The Central Characters of the Novel “Mafroor” in the Light of Narcissistic Tendencies and Abnormality - Rehman, Noor ur; Marjan, Asal (Makhz (Research Journal), 2025)
"Mafroor" by Mia Said Rasool Rasa is a remarkable novel in terms of theme, technique, character portrayal, and artistic expression. First published in 1963, the novel presents a vivid depiction of the lives of fugitives. The central characters, Umray and Gulabo, dominate the narrative. Both characters are portrayed as having intense narcissistic tendencies and signs of abnormality. Narcissism, as we know, exists in human personality in a developmental spectrum—ranging from ordinary expressions to more pathological extremes. It often manifests as a self-centered behavior pattern that revolves solely around personal desires and needs. The characters of Umray and Gulabo reflect precisely this type of narcissistic and abnormal psychology. The writer has analyzed these personalities through the lens of psychology—particularly by drawing upon Sigmund Freud’s theories. Based on psychological reasoning, the analysis reveals the narcissistic tendencies and psychological deviations in both characters, making their portrayal not just fictional but deeply psychological and symbolic as well.